Methods for powering bioelectronic microdevices. Issue 3 (November 2018) - Lee, Pui Mun; Xiong, Ze; Ho, John
Bioelectronic microdevices are an emerging class of biomedical devices miniaturized at the scale of a millimeter or less, which promise new capabilities for monitoring and treating human disease. Although rapid progress has been made in the sensing and actuation capabilities of microdevices, a major technological challenge remains in the way that these devices are powered within the body. In this review, we revisit the power requirements of microdevices, describe current methods for storing, transferring or harvesting energy in microdevices, provide an overview of emerging powering approaches and discuss the promise of microdevices in biomedicine.